CACNA1C Polymorphism (rs2283291) Is Associated with Schizophrenia in Chinese Males: A Case-Control Study. (1st April 2019) - Zhu, Xiaojing; Li, Rixin; Kang, Guojun; Kang, Qi; Rao, Wenwang; Yang, Mingjia; Cao, Bonan; Zhang, Mingyuan; Sun, Yaoyao; Wang, Yueying; Chen, Xin; Yu, Yaqin; et al.
Abstract : Recent research has shown that prenatal famine exposure may be one of the risk factors for schizophrenia and that people born in famine years may be at an increased risk of schizophrenia due to alteration of the DNA methylation of genes. In this study, the association of rs2283291/rs4648635 and the incidence of schizophrenia and prenatal famine exposure at the genetic level were investigated to provide clues to the pathogenesis of schizophrenia. A total of 960 participants were recruited, comprising 473 prenatal famine-exposed individuals (225 patients and 248 controls) and 487 prenatal non-famine-exposed individuals (220 patients and 267 controls). The association of prenatal famine, schizophrenia, and their interaction with DNA methylation levels was analyzed using SPSS and GMDR software. Gender stratification analysis revealed a significant association between the rs2283291 genotype and schizophrenia in male patients (P = 0.017 ), and difference still existed after correction by the Bonferroni method. It was also found that an increasing risk of schizophrenia was associated with rs2283291 in males (OR: 1.62, 95% CI: 1.13-2.33, P = 0.0086, AIC = 669.7 ) in an overdominant model. The results of gene-environment interaction and gene-gene interaction revealed no association with the risk of schizophrenia. This study reported for the first time that rs2283291 was associated with schizophrenia in Chinese males.